Response of human dental pulp to calcium hydroxide paste preceded by a corticosteroid/ antibiotic dressing agent - Elisa Maria Aparecida Giro; Juliana Oliveira Gondim; Josimeri Hebling; Carlos Alberto de Souza Costa (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the treatment with corticosteroid/antibiotic dressing in pulpotomy with calcium hydroxide. Methods: Forty-six premolars were pulpotomized and randomly assigned into 3 groups. In Group I pulpal wound was directly capped with calcium hydroxide, and Group II and Group III received corticosteroid/antibiotic dressing for 10 min or 48 h, respectively, before pulp capping. Teeth were processed for histological analysis after 7, 30 or 60 days to determine inflammatory cell response, tissue disorganization, dentin bridge formation and presence of bacteria. Attributed scores were analyzed by Kruskal-Wallis and Mann-Whitney tests (α=0.05). Results: On the 7th day, all groups exhibited dilated and congested blood vessels in the tissue adjacent to pulpal wound. The inflammatory cell response was significantly greater in Group III (p<0.05). On the 30th day, in all groups, a thin dentin matrix layer was deposited adjacent to the pulpal wound and a continuous odontoblast-like cell layer underlying the dentin matrix was observed. On the 60th day, all groups presented a thick hard barrier characterized by an outer zone of dystrophic calcification and an inner zone of tubular dentin matrix underlined by a defined odontoblast-like cell layer. Conclusions: Within the limitations of present study, considering that the treatment was performed in healthy teeth, it may be concluded that the use of a corticosteroid/antibiotic dressing before remaining tissue protection with calcium hydroxide had no influence on pulp tissue healing